Human intestinal mucus proteins isolated by transanal irrigation and proctosigmoidoscopy (2014)
Human intestinal mucus essentially consists of a network of Mucin2 glycoproteins embedded in many lower molecularweight proteins. This paper contributes to the proteomic study of human intestinal mucus by comparing two sample collectionmethods (transanal irrigation and brush cytology during proctosigmoidoscopy) and analysis techniques (electrophoresis anddigestion in solution). The entire sample collection and treatment process is explained, including protein extraction, digestion anddesalination and peptide characterisation using a nanoAcquity UPLC chromatograph coupled to an HDMS spectrometer equipped with a nanoESI source. Collecting mucus via transanal irrigation provided a larger sample volume and protein concentration from a single patient. The proctosigmoidoscopy sample could be analysed via digestion in solution after depleting albumin. The analysisindicates that a simple mucus lysis method can evaluate the electrophoresis and digestion in solution techniques. Studying human intestinal mucus complexes is important because they perform two essential survival functions for humans as the first biochemical and physical defences for the gastrointestinal tract and a habitat for intestinal microbiota, which are primarily hosted in the colon and exceeds the human genetic information and cell number 100- and 10-fold (1).